Verification and application of qPCR and viability-qPCR for Legionella monitoring in evaporative cooling systems complementing the conventional culture method - J. Redwitz; P. Streich; M. Zamfir; S.M. Walser-Reichenbach; M. Seidel; C.E.W. Herr; S. Heinze; C. Quartucci (Science of The Total Environment, 2024)

Characterisation of the static offset in the travelling wave in the cochlear basal turn - Takeru Ota; Fumiaki Nin; Samuel Choi; Shogo Muramatsu; Seishiro Sawamura; Genki Ogata; Mitsuo P. Sato; Katsumi Doi; Kentaro Doi; Tetsuro Tsuji; Satoyuki Kawano; Tobias Reichenbach; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
In mammals, audition is triggered by travelling waves that are evoked by acoustic stimuli in the cochlear partition, a structure containing sensory hair cells and a basilar membrane. When the cochlea is stimulated by a pure tone of low frequency, a static offset occurs in the vibration in the apical turn. In the high-frequency region at the cochlear base, multi-tone stimuli induce a quadratic distortion product in the vibrations that suggests the presence of an offset. However, vibrations below 100 Hz, including a static offset, have not been directly measured there. We therefore constructed an interferometer for detecting motion at low frequencies including 0 Hz. We applied the interferometer to record vibrations from the cochlear base of guinea pigs in response to pure tones. When the animals were exposed to sound at an intensity of 70 dB or higher, we recorded a static offset of the sinusoidally vibrating cochlear partition by more than 1 nm towards the scala vestibuli. The offset’s magnitude grew monotonically as the stimuli intensified. When stimulus frequency was varied, the response peaked around the best frequency, the frequency that maximised the vibration amplitude at threshold sound pressure. These characteristics are consistent with those found in the low-frequency region and are therefore likely common across the cochlea. The offset diminished markedly when the somatic motility of mechanosensitive outer hair cells, the force-generating machinery that amplifies the sinusoidal vibrations, was pharmacologically blocked. Therefore, the partition offset appears to be linked to the electromotile contraction of outer hair cells.

The Influence of Land Use Change on Landslide Susceptibility Zonation: The Briga Catchment Test Site (Messina, Italy) - P. Reichenbach; C. Busca; A. C. Mondini; M. Rossi (Environmental Management, 2014)

Introduction to the special issue “Landslides: forecasting, hazard evaluation, and risk mitigation” - M. Parise; G. R. Iovine; P. Reichenbach; F. Guzzetti (Natural Hazards, 2012)

Rockfall hazard assessment along a road in the Sorrento Peninsula, Campania, southern Italy - B. Palma; M. Parise; P. Reichenbach; F. Guzzetti (Natural Hazards, 2012)

Rock fall hazard along the railway corridor to Jerusalem, Israel, in the Soreq and Refaim valleys - O. Katz; P. Reichenbach; F. Guzzetti (Natural Hazards, 2011)

Comparing Landslide Maps: A Case Study in the Upper Tiber River Basin, Central Italy - F. Guzzetti; M. Cardinali; P. Reichenbach; A. Carrara (Environmental Management, 2000)

Use of GIS Technology in the Prediction and Monitoring of Landslide Hazard - A. Carrara; F. Guzzetti; M. Cardinali; P. Reichenbach (Natural Hazards, 1999)